Peptide Microstructures: Capillary Force‐Driven, Hierarchical Co‐Assembly of Dandelion‐Like Peptide Microstructures (Small 24/2015). Issue 24 (June 2015) - Wang, Yuefei; Huang, Renliang; Qi, Wei; Xie, Yanyan; Wang, Mengfan; Su, Rongxin; He, Zhimin
<x xml:space="preserve">Abstract</x> Elegant dandelion‐like peptide microstructures are formed by W. Qi and co‐workers by the sequential, combinatorial co‐assembly of diphenylalanine (FF) and ferrocene‐diphenylalanine (Fc‐FF). In the SEM image shown, FF microtube networks are colored yellow, FF microtube arrays are colored green and serve as the scapes of the dandelion flowers, and Fc‐FF nanofibers, serving as the flower heads, are shown in white. These homogeneous FF microtubes with precisely tailored diameters and wall thicknesses are synthesized on page 2893 by controlling the degree of supersaturation and water content.